The development and types of social knowledge - Hausner, Jerzy (Journal of Public Governance, 2013)
The article focuses on types of social knowledge. Apart from analytic and systemic thinking, understanding of social beings requires modular thinking, which involves primarily a new interpretation of social reality. To recognize the existence of several types of social knowledge is tantamount to rejecting the concept of determinism in the operation of the social world. If we renounce determinism in favour of probabilism or contingency, i.e. an indispensable necessity, we admit, in principle, that there may exist a series of situations (states), which are not random and which open up a range of entirely new possibilities.